2014
DOI: 10.1080/09500693.2013.827817
|View full text |Cite
|
Sign up to set email alerts
|

‘She Has to Drink Blood of the Snake’: Culture and prior knowledge in science|health education

Abstract: In this analysis, we argue that science education should attend more deeply to youths' cultural resources and practices (e.g. material, social, and intellectual). Inherent in our argument is a call for revisiting conceptions of 'prior knowledge' to theorize how people make sense of the complex ecologies of experience, ideas, and cultural practices that undergird any learning moment. We illustrate our argument using examples from the domain of personal health, chosen because of its tremendous societal impact an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 23 publications
1
5
0
Order By: Relevance
“…As we describe below, our work is situated in and influenced by the Reggio Emilia philosophy and social constructivist frameworks as the latter is the widely accepted U.S. norm for early childhood practitioners and researchers. Our works, and especially those detailed in this article, are well aligned to the work Bricker, Reeve and Bell (2014) used with older learners, concluding that "'youths' 'prior knowledge' cannot be separated from the cultural milieu in which it is situated" [70] (p. 1458). The indications are straightforward-we, as early childhood science and mathematics educators need to expand our conceptions of knowledge beyond merely cognitive aspects to be equally inclusive and informed by learners' social and cultural knowledges, as the fields of science and mathematics education in older grades has done [43,69,71,72].…”
Section: The Critical Science and Mathematics Early Childhood (Csmec)supporting
confidence: 66%
“…As we describe below, our work is situated in and influenced by the Reggio Emilia philosophy and social constructivist frameworks as the latter is the widely accepted U.S. norm for early childhood practitioners and researchers. Our works, and especially those detailed in this article, are well aligned to the work Bricker, Reeve and Bell (2014) used with older learners, concluding that "'youths' 'prior knowledge' cannot be separated from the cultural milieu in which it is situated" [70] (p. 1458). The indications are straightforward-we, as early childhood science and mathematics educators need to expand our conceptions of knowledge beyond merely cognitive aspects to be equally inclusive and informed by learners' social and cultural knowledges, as the fields of science and mathematics education in older grades has done [43,69,71,72].…”
Section: The Critical Science and Mathematics Early Childhood (Csmec)supporting
confidence: 66%
“…As Holland and Lave note, social practice theory “…emphasizes the importance of cultural activities in framing human cognition and social activity, but goes on to inquire into how persons develop in practice…it focuses on how history‐in‐person takes shape in local practice interpreted according to cultural activities” (p. 5). When constructing the Cultural Learning Pathways Framework, we also drew heavily on the concepts of life‐long learning (learning across one's lifespan), life‐wide learning (learning across the various contexts that people navigate), and life‐deep learning (learning as connected to personal and cultural value systems; see Banks et al, ; Bricker et al, in ).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Yet, we argue that these accounts are exactly what are needed in order to better understand aspects of youths' STEM‐related learning (e.g., Bell et al, ; Bricker & Bell, ; Nasir, ; Warren, Ballenger, Ogonowski, Rosebery, & Hudicourt‐Barnes, ), as well as to leverage the details and nuances of these learning pathways in the design of school science related learning environments (e.g., Bang, Medin, Washinawatok, & Chapman, ; Calabrese Barton, ; Rosebery, Warren, Ballenger, & Ogonowski, ; Tzou, Bricker, & Bell, ). Assuming that the science education community considers youths' experiences, interests, cultural practices, and linguistic patterns, for example, as part of their prior knowledge (see Bricker, Reeve, & Bell, in ), and that the field values building on learners' prior knowledge during school science instruction (see Bransford, Brown, & Cocking, ), how do we, as science educators, learn about and characterize youths' STEM‐related trajectories across contexts and timescales so that we can help build better STEM‐related learning bridges?…”
mentioning
confidence: 99%
“…The emergent themes have implications for connecting students with Black culture and the culture of other people of colour. Bricker et al's (2014) makes a case for connecting the science content of schools with students' prior knowledge by considering practices related to their homes. They found that for all 13 students 'the young people had prior knowledge about health that was multidimensional and situated in personal, academic, and cultural contextssuch as a family member's advice, cultural and media messages about weight loss, or personal experiences of health and illness' (Bricker et al, 2014(Bricker et al, , p. 1460.…”
Section: Discussionmentioning
confidence: 99%
“…Bricker et al's (2014) makes a case for connecting the science content of schools with students' prior knowledge by considering practices related to their homes. They found that for all 13 students 'the young people had prior knowledge about health that was multidimensional and situated in personal, academic, and cultural contextssuch as a family member's advice, cultural and media messages about weight loss, or personal experiences of health and illness' (Bricker et al, 2014(Bricker et al, , p. 1460. Bricker et al (2014) note that the connection between science and health can create a common ground because decisions made about health often take place in the home and community environments and capitalise on the cultural resources of students.…”
Section: Discussionmentioning
confidence: 99%